PEMANFAATAN TEORI KOMUNIKASI PERSUASIF PADA PENELITIAN E-COMMERCE DI ERA DIGITAL - Ira Mirawati (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
Communication persuasive is used for affect the beliefs, values, and attitudes of consumers.Many theories of persuasive communication are closely that related to the marketing of a product or service. The aims of this paper is to describe several persuasive communication theories that have developed and are widely used for the researches on e-commerce in the digital era.The method that used in this paper is a literature study with a descriptive qualitative approach with data collection carried out from April to June 2021. The result shows, the theory that generally used is start from the powerful effect model, the effect of synthetic experience, elaboration likelihood model, cognitive dissonance, and attribution. The theories of communication in this paper are applied to the several e-commerce in Indonesia, both in the advertising content that displayed to the audience, but also on interaction features in service applications of e-commerce.